2013
DOI: 10.1016/j.tins.2013.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of neuronal activity by phosphorylation of the K–Cl cotransporter KCC2

Abstract: The K–Cl cotransporter KCC2 establishes the low intraneuronal Cl− levels required for the hyperpolarizing inhibitory postsynaptic potentials mediated by ionotropic g-aminobutyric acid receptors (GABAARs) and glycine receptors (GlyRs). Decreased KCC2-mediated Cl− extrusion and impaired hyperpolarizing GABAAR- and/or GlyR-mediated currents have been implicated in epilepsy, neuropathic pain, and spasticity. Recent evidence suggests that the intrinsic ion transport rate, cell surface stability, and plasmalemmal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
176
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 188 publications
(184 citation statements)
references
References 114 publications
(183 reference statements)
6
176
0
Order By: Relevance
“…This is in line with the observation of phosphorylated Ser 937 and likely Thr 934 in adult brain tissue (57). So far, phosphorylation mainly affected trafficking or the half-lives of KCC2 (5,36). In contrast to these findings, the increased activity of KCC2 T934D or KCC2 S937D was not paralleled by an increase in total amount or cell surface expression of the transporter (Figs.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is in line with the observation of phosphorylated Ser 937 and likely Thr 934 in adult brain tissue (57). So far, phosphorylation mainly affected trafficking or the half-lives of KCC2 (5,36). In contrast to these findings, the increased activity of KCC2 T934D or KCC2 S937D was not paralleled by an increase in total amount or cell surface expression of the transporter (Figs.…”
Section: Discussionsupporting
confidence: 89%
“…The kinase inhibitors lavendustin A, genistein (32), or staurosporine (33) altered KCC2 transport activity in cultured hippocampal neurons, and calyculin (34) and okadaic acid (35), two potent phosphatase inhibitors, blocked activation of KCCs by cell swelling. The important role of phosphorylation was corroborated by the regulatory role of several identified phosphorylation sites in KCC2 (36). Phosphorylation of human threonines Thr 906 and Thr 1007 reduced the intrinsic transport activity of KCC2 (37,38).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…The "ionic plasticity" of GABAergic signaling involves not only the passive flux of Cl − ions through membrane channels but also, a number of ion transporters that regulate [Cl − ] i . Furthermore, this mechanism is under the control of intracellular signaling cascades that regulate the expression patterns as well as functional properties of ion transporters and channels (5,6). With regard to long-term ionic modulation of GABAergic transmission, a case in point is the decrease in [Cl − ] i that is generally thought to take place during maturation of most central neurons.…”
mentioning
confidence: 99%
“…Gain-of-function mutations, however, appear to promote the activity of NKCC1 over KCC2 at this older developmental stage (Figure 3(d)), as indicated by the inhibitor data. Although the molecular details of such a connection between glycine receptor strength and altered functionality of NKCC1/KCC2 remain to be characterized, it has been reported that glycine receptor activity and solute carrier function correlate in late differentiating neurons [24], and a shift in solute carrier expression and activity patterns upon brain lesions or neuropathy has also been reported [2529]. …”
Section: Resultsmentioning
confidence: 99%